2021
DOI: 10.1016/j.pacs.2020.100226
|View full text |Cite
|
Sign up to set email alerts
|

Detection of disbonds in adhesively bonded aluminum plates using laser-generated shear acoustic waves

Abstract: Adhesively bonded metals are increasingly used in many industries. Inspecting these parts remains challenging for modern non-destructive testing techniques. Laser ultrasound (LU) has shown great potential in high-resolution imaging of carbon-reinforced composites. For metals, excitation of longitudinal waves is inefficient without surface ablation. However, shear waves can be efficiently generated in the thermo-elastic regime and used to image defects in metallic structures. Here we present a compact LU system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Visualization of wrinkles and local ply angle orientation [69] : (h) - photograph of wrinkled sample, (i) – LU image of the sample structure overlapped with the locally computed ply angle. Evaluation of disbonds in adhesively bounded aluminum plates using laser-generated shear acoustic waves [70] : (j) – diagram of the sample, (k) – measurement diagram, (l) – LU C-scan at the depth of plate bounding, indicating a Teflon inclusion in the structure. …”
Section: Methodsmentioning
confidence: 99%
“…Visualization of wrinkles and local ply angle orientation [69] : (h) - photograph of wrinkled sample, (i) – LU image of the sample structure overlapped with the locally computed ply angle. Evaluation of disbonds in adhesively bounded aluminum plates using laser-generated shear acoustic waves [70] : (j) – diagram of the sample, (k) – measurement diagram, (l) – LU C-scan at the depth of plate bounding, indicating a Teflon inclusion in the structure. …”
Section: Methodsmentioning
confidence: 99%
“…They can be calculated as follows, and satisfy the excitation conditions for a line source under the thermoelastic mechanism [28] : where and are the normalised amplitudes of the longitudinal and shear waves, respectively; is the included angle between the ultrasound and the surface direction; and and are the slowness defined by the reciprocal of the wave speeds and , respectively. It was previously demonstrated that in a 3-D situation, the ultrasound directivity generated by a line source in the 2-D plane perpendicular to the length of the laser line source is similar to that of the point source [17] , [29] , [30] . To study the influence of the directivity of different wave modes, the calculated half-magnitude directivity patterns of longitudinal and shear waves for aluminum are shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…Second, the LUT provides not only possibilities for both wide-band and narrow-band generation, but also for multi-wave-mode generation. In addition, different modes of waves can carry physical information with special directivity patterns [14] , [15] , [16] , relating to the location of surface cracks, thickness of the specimen, and internal defects [17] , [18] , [19] . The LUT also has a high spatial resolution [20] , which is important for detecting and imaging tiny defects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig.1 (a), in previous LU-SAFT studies, the generation (represented by “G” and the red arrows) and the detection (represented by “D” and the green arrows) are coincident (scenario ①). In practical LU tests, to avoid the thermal expansion’s influence caused by generation laser irradiation on the detection point, the generation and detection laser spots are often separate [6] , [22] as shown by scenario ② in Fig.1 (a). In both scenarios, the actual ultrasound propagation paths are indicated by solid lines with arrows, while the equivalent ultrasound propagation paths in the exploding source approximation of the F-SAFT algorithm are indicated by dashed lines with arrows.…”
Section: Theorymentioning
confidence: 99%